Dogmagic - Webb, Holly (New York : Scholastic, 2009)
Eleven-year-old Lottie and her familiar, Sofie the dachshund, wonders if she can trust her new friend Ruby with the secret of her uncle's magical pet shop.
Booklist
4.0
3-6.
3-6
Keywords: Dogs -- Juvenile fiction; Magic -- Juvenile fiction; Pet shops -- Juvenile fiction; Dogs -- Fiction; Magic -- Fiction; Pet shops -- Fiction; Dogs -- Fiction; Magic -- Fiction; Pet shops -- Fiction